The Geochemical specificities of distribution of macroelements within the soils of undisturbed landscapes of middle ural (on the example of “Basegi” preserve) - I. A. Samofalova; O. B. Rogova; O. A. Luzyanina; A. T. Savicthev (Бюллетень Почвенного института им. В.В. Докучаева, 2016)
The geochemical specificities of mountainous soils of Middle Ural on the example of Basegi Ridge were considered in this work. We calculated and analyzed geochemical coefficients of accumulation, subsurface weathering, eluviation and oxidation. It is shown that soil forming processes on Severniy Baseg Mountain don’t lead to the clear differentiation of the profile according to the content of one or another microelements. The level of concentrations of elements in landscapes was increased from elluvial to transaccumulative. This was determined by the increasing role of lateral distribution of concentration of chemical elements in mountainous ecosystems. This is confirmed by the calculated accumulation coeffecients and also by the results of cluster analysis. It shows that there are higher concentrations of Al, Fe, K, Ca, Mg, Mn in the soils of forest-mountainous belt, comparing to soils of goltsy altitudinal belt and subgoltsy altitudinal belt, and comparing to alpine belt. The analysis of the original data and literature sources confirmed that the climate change in the end of late Holocene affected dramatically on the climate change of mountainous part of western macroslope of Middle Ural.